Work hard, play hard: how sexually differentiated microglia work to shape social play and reproductive behavior - Sullivan, Olivia; Ciernia, Annie Vogel (Frontiers in Behavioral Neuroscience, 2022)
Microglia are brain-resident immune cells that play a critical role in synaptic pruning and circuit fine-tuning during development. In the adult brain, microglia actively survey their local environment and mobilize inflammatory responses to signs of damage or infection. Sex differences in microglial gene expression and function across the lifespan have been identified, which play a key role in shaping brain function and behaviour. The levels of sex hormones such as androgens, estrogens and progesterone vary in an age-dependent and sex-dependent manner. Microglia respond both directly and indirectly to changes in hormone levels, altering transcriptional gene expression, morphology and function. Of particular interest is microglial function in brain regions that are highly sexually differentiated in development such as the amygdala as well as the pre-optic and ventromedial hypothalamic regions. With a focus on hormone-sensitive developmental windows, this review compares male and female microglia in the embryonic, developing, and adult brain with a particular interest in the influence of sex hormones on microglial wiring of social, reproductive, and disordered behaviour circuits in the brain.